Islamization and Social Change Among The Suku Anak Dalam in Bukit Dua Belas National Park (TNBD), Sarolangun Regency, Jambi - Zulgafrin (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
This article examines the Islamization of the Suku Anak Dalam and the social transformations that accompanied this process. The study employs a qualitative approach using the historical method to reconstruct past events experienced by the Suku Anak Dalam and to analyze the socio-cultural changes that followed. Data were collected through oral history, including testimonies from customary leaders (Tumenggung) and community members who directly experienced the process of Islamization, as well as relevant contemporary documents available in the field. The research provides an analysis of the condition of the Suku Anak Dalam before and after the establishment of Taman Nasional Bukit Dua Belas (TNBD). Prior to the creation of TNBD, the Suku Anak Dalam had inhabited the forest for generations, relying on it as their primary source of livelihood. However, after the establishment of the national park and subsequent land-use changes, forest resources declined significantly. As a result, the community could no longer sustain their traditional way of life. Several factors contributed to religious conversion, including intermarriage with Muslim communities, the requirement to convert prior to marriage, and economic pressures linked to diminishing forest resources. Following conversion, significant social changes occurred, including the adoption of settled living patterns and the abandonment of certain traditional cultural and religious practices.